α emitter-labeled radiopeptides for targeted α therapy of tumors - Cieslik, Patrick; Wängler, Björn; Wängler, Carmen (Journal of medicinal chemistry, 2025)
In the area of nuclear medicine diagnosis and therapy of tumors, peptides play a central role as tumor-homing compounds, enabling high affinity and specific accumulation of the agents, thereby laying the foundation for successful imaging and therapy. Due to their favorable chemical and biological properties, peptides play an essential role as radionuclide carriers. For decades, therapy in nuclear medicine was based on the use of β- emitter-labeled peptides as receptor-specific therapeutics. This paradigm is beginning to change in the direction of α emitter-labeled analogs, as these demonstrate a considerably higher therapeutic efficiency. However, their application also poses significant challenges that need to be addressed in the future to unleash the full potential of this form of therapy. This perspective discusses the advantages of α-emitter-carrying radiopeptides for the targeted α therapy (TAT) of tumors and the remaining challenges that need to be addressed by future research.